Interdental alveolar bone density in bruxers, mild bruxers, and non-bruxers affected by orthodontia and impaction as influencing factors. - Shokry, Shereen; Rahman, Ghousia; Kandil, Hossam; Hakeem, Hanan; Al-Maflehi, Nassr (Journal of Oral Research; Vol 4 No 6DO - 10.17126/joralres.2015.073, 2015)
Aim: To assess the interdental alveolar bone density within specific regions of interest in the mandible of bruxers, mild bruxers and non-bruxers in absence or presence of influencing factors, such as orthodontia and impaction. Materials and methods: The study consisted of 104 subjects (64 bruxers and 40 controls) from the female students in the Faculty of Dentistry. Students were classified into bruxers, non-bruxers, and mild bruxers. The presence of modifying factors, such as impacted mandibular third molars and/or current or recent orthodontic treatment were identified. Panoramic radiographs were obtained, and the mean bone density values of interdental alveolar bone were measured using ImageJ software. Results: Non-bruxers had the highest mean bone density in all measured regions. The mesial aspect of the second premolar was an area of higher mean bone density in bruxers and in mild bruxers, compared to non-bruxers. In the presence of orthodontic treatment, the mean bone density in non-bruxers surpassed that of bruxers and mild bruxers. Conclusion: Bruxism, whether mild or severe decreased the interdental mean bone density in the studied regions of interest. The presence of influencing factors affected the interdental mean bone density.
Keywords: Bruxism, Bone density, Orthodontic treatment, Tooth impaction, Panoramic radiography.